“The man who wasn’t there”—and was “out there”: Chigurh as cinematic figure - Nicole Cloarec (Revue LISA)
Notwithstanding Joel Coen’s tongue-in-cheek comment that his film is “about a good guy, a bad guy, and a guy in between”, the main characters of No Country for Old Men have evinced much perplexity. In particular, Chigurh, who has been deemed one of the most chilling villains in cinema history, defies any univocal archetypal definition that would readily apply to such character type. The present article focuses on the character of Chigurh in the Coens’ film. After examining the diversity of interpretations that have sought to account for his character, it contends that Chigurh’s enigmatic ambivalence is part and parcel of his characterisation. More specifically, it throws light on the character’s ambivalence as a cinematic entity, that is, not so much as a direct personification of moral and philosophical issues as the embodiment of filmic figures and devices that are displayed to convey the film’s worldview.